Axonal Transport and Mitochondrial Function in Neurons - Mandal, Amrita; Drerup, Catherine M. (Frontiers in Cellular Neuroscience, 2019)
The complex and elaborate architecture of a neuron poses a great challenge to the cellular machinery which localizes proteins and organelles, such as mitochondria, to necessary locations. Proper mitochondrial localization in neurons is particularly important as this organelle provides energy and metabolites essential to form and maintain functional neural connections. Consequently, maintenance of a healthy pool of mitochondria and removal of damaged organelles are essential for neuronal homeostasis. Long distance transport of the organelle itself as well as components necessary for maintaining mitochondria in distal compartments are important for a constant supply of healthy mitochondria at the right time and place. Accordingly, many neurodegenerative diseases have been associated with mitochondrial abnormalities. Here we review our current understanding on transport-dependent mechanisms that regulate mitochondrial replenishment. We focus on axonal transport and import of mRNAs and proteins destined for mitochondria as well as mitochondrial fusion and fission to maintain mitochondrial homeostasis in distal compartments of the neuron.